2018
DOI: 10.1007/s11099-018-0818-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of phenolic acids on the photosynthetic characteristics and growth of Populus × euramericana cv. 'Neva' seedlings

Abstract: Populus × euramericana cv. 'Neva' is an important tree species in northern China. In the study, we used its potted oneyear-old seedlings as experimental material and established three treatments (CK, 0.5X, and 1.0X) according to the concentrations of phenolic acids in order to examine the effects of different concentrations on the photosynthetic characteristics and growth of poplar. With increasing concentrations of phenolic acids, the net photosynthetic rate, stomatal limitation, transpiration rate, apparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Studies have shown that allelochemicals inhibit the synthesis of indoleacetic acid and gibberellin, thus hindering germination in target plants [35]. Similarly, allelochemicals may affect plant photosynthesis, and further alter cell respiration and metabolism, thereby affecting plant growth [36]. These studies on allelopathic mechanisms support our experimental results.…”
Section: Effect Of Leaf Litter Water Extract On Seed Germination and supporting
confidence: 88%
“…Studies have shown that allelochemicals inhibit the synthesis of indoleacetic acid and gibberellin, thus hindering germination in target plants [35]. Similarly, allelochemicals may affect plant photosynthesis, and further alter cell respiration and metabolism, thereby affecting plant growth [36]. These studies on allelopathic mechanisms support our experimental results.…”
Section: Effect Of Leaf Litter Water Extract On Seed Germination and supporting
confidence: 88%
“…This finding may be related to the promotion of Chl content by R. delavayi mycorrhizal fungi (Lin et al 2011, Jing 2013. Under normal circumstances, PN decreases along with the Chl content (Wang 2015, Xie et al 2018. In this study, under the three kinds of phenolic stress, Chl a, Chl b, and total Chl were extremely negatively correlated with PN, and the results of the RDA analysis showed that Chl a was the main factor influencing the photosynthetic characteristics ( Fig.…”
Section: Photosynthetic Pigmentsmentioning
confidence: 59%
“…Photosynthesis may be inhibited by reducing the amount of functional reaction centers of PSII (Dwyer et al 2012). The maximum quantum yield of the PSII primary photochemistry was depressed, which has yet to be studied (Lu et al 2018, Xie et al 2018. PA had no effect on the leaf stomata of R. delavayi.…”
Section: Stomatal Characteristicsmentioning
confidence: 99%
“…We can conclude that high temperature seriously damaged the cells of tomato seedlings, and heat shock could alleviate heat stress. Antioxidant enzymes, such as POD, CAT, and SOD, are the most important enzymes for scavenging free radicals, maintaining the balance between free radical production and elimination in plant cells (Xie et al 2018). There have been many reports on the comparative effects of SOD, CAT, and POD activities exposed to high temperature stress (Zhu et al 2010, Yuan et al 2011, Wang et al 2014.…”
Section: Discussionmentioning
confidence: 99%